A miniaturized assay for influenza neuraminidase‐inhibiting antibodies utilizing reverse genetics‐derived antigens - Sandbulte, Matthew R. (Influenza Other Respir Viruses, 2009)
Background  Antibodies to neuraminidase (NA) contribute to protection during influenza virus infection, but NA inhibition (NI) titers are not routinely analyzed in vaccine trials. One reason is the cumbersome nature of the conventional thiobarbituric acid (TBA) NI assay, which uses chemical methods to quantify free sialic acid following incubation of NA with substrate in the presence of serum. In addition, the assay is complicated by the need to use virus of a hemagglutinin (HA) subtype novel to the host to detect NA‐specific antibodies only. Objectives  Our primary objectives were to miniaturize the colorimetric NI assay to a format suitable for quantitative analysis of large numbers of samples, and validate the specificity and sensitivity of the miniaturized format with ferret and human sera. An additional aim was to use reverse genetics to construct HA‐mismatched viral reagents bearing NA of recent influenza A vaccine strains and H6 HA. Results  Analysis of ferret antisera by the miniaturized assay demonstrated sensitivity and specificity comparable with the conventional assay. Similar increases in the NI titers in sera from vaccinated human volunteers were measured in miniaturized and conventional assays. Inactivated and live‐attenuated vaccines increased NI titers against a given subtype at approximately the same rate. Conclusions  The reagents and miniaturized format of the TBA method described here provide a platform for practical serological monitoring of functional antibodies against NA.